Risk Analysis Based on Failure Mode And Effect Analysis (FMEA) in the ISO 9001:2015 Quality Management System On Toll Road Projects (Case Study: Toll Road Cikupa, STA 32+100 – 36+300) - Henoch Leindrio Cornelis; Endah Kurniyaningrum; Bambang Endro Yuwono; Inavonna Inavonna (Eduvest - Journal of Universal Studies, 2025)
Toll roads play a crucial role in supporting national economic mobility and growth. Quality risks such as grain leakage, crocodile skin cracks, curls, grooves, removal of asphalt layers, and collapses frequently occur on the Tangerang-Merak Toll Road, specifically in the Balaraja-Cikupa section. This study aims to integrate the Failure Mode and Effect Analysis (FMEA) method with the ISO 9001:2015 standard to enhance risk management within the quality management system of toll road projects. It also evaluates the model’s effectiveness in reducing potential failures, improving quality, and aiding decision-making. The study focuses on selected clauses from the ISO 9001:2015 quality management system, including planning and controlling operations, product and service requirements, control of externally provisioned processes, and involvement of production and service providers. The Risk Priority Number (RPN) is used to analyze potential failure modes, measured by severity, occurrence, and detection. At the study site, the highest RPN value was 294, linked to an asphalt mixture that was insufficiently liquid. The failure modes most strongly related to quality degradation were cracks and deformations undetected during initial inspections (X2-9), with a correlation of 0.922 and a significance value of 0.000. The combined effect of all free variables (X1, X2, X3, X4) on the decrease in work quality at the site (Y) accounted for 70.7%. This integration of FMEA and ISO 9001:2015 provides a valuable framework for improving risk management and quality assurance in toll road projects.